Relating leaf spectral reflectance to its color: an inquiry-based activity to enhance understanding of electromagnetic radiation. (2nd January 2019) - Sivanpillai, Ramesh; Whitman, Ronald D.
Abstract: Understanding the concept of electromagnetic radiation (EMR) and its interaction with matter (absorption, reflection, and transmission) can be difficult for students in seventh and eighth grade physical science classes. This inquiry-based activity (IBA) is aimed at improving their understanding of these concepts by exploring the interaction of EMR with leaves of different plant species or health conditions. Incorporating at least two different types of leaves from the local environment and measuring their interaction with EMR peaks student interest in this activity. After completing this IBA, students will see how objects interact in different regions of the electromagnetic spectrum and gain a better understanding of phenomena such as reflection and absorption. Further, this IBA can help them understand how human eyes perceive different colors. This activity can be expanded by a biology teacher to include a discussion about leaf pigments and how their interaction with EMR determines the colors of leaves. Concepts covered in this IBA can be related to remote sensing science and how sensors on board satellites collect Earth Observation data.